Corrosion behavior of porous silicon nitride ceramics in different atmospheres. Issue 5 (1st April 2017) - Hou, Xinmei; Wang, Enhui; Li, Bin; Chen, Junhong; Chou, Kuo-Chih
Abstract: The corrosion behavior of silicon nitride (Si3 N4 ) ceramics with a porosity of 46% at 1200–1500 °C under different conditions including dry O2, O2 containing 20 vol% H2 O and Ar containing 20 vol% H2 O is compared. The results show that porous Si3 N4 ceramics exhibit good oxidation resistance up to 1200 °C. Their corrosion behavior varies depending on the temperature and atmosphere. Water vapor can obviously affect the morphology of the reaction product and thus accelerate the corrosion rate due to its specific inward diffusion mechanism and devitrified effect at high temperature. In view of the reaction kinetics, it proceeds in a diffusion-controlled manner in dry O2 while follows the parabolic-linear law at water-containing atmosphere. Furthermore, a new model considering both oxidation and volatilization reactions is established. These provide a baseline for expanding the application fields of non-oxide porous ceramics such as Si3 N4 and silicon carbide (SiC) etc.